Special issue in honour of Prof. Reto J. Strasser - Seasonal monitoring of PSII functionality and relative chlorophyll content on a field site in two consecutive years: A case study of different oak species - S. KOLLER; V. HOLLAND; W. BRÜGGEMANN (Photosynthetica, 2020)
In search for practical silvicultural management tools to identify alternative tree species for predicted Central European climate conditions, a cross-species survey with five evergreen, semi-evergreen, and deciduous Quercus taxa with contrasting morphological leaf traits was performed. Fast chlorophyll fluorescence induction of PSII and relative leaf chlorophyll contents were performed to assess the overall plant vitality at any point in time during two complete vegetation periods in consecutive years (2012 and 2013). Maximum photochemical efficiency of PSII and the performance index on absorption base showed a very conservative relationship to each other and a similar intra-annual progress in all deciduous species, but with a different speed of increase and decrease during leaf development and senescence and thus a different length of vegetation period. The intra-annual variability of OJIP and chlorophyll content parameters is considered with respect to the practicability of measurements in the field for management purposes.